2019
DOI: 10.1007/s10278-019-00300-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dynamic Change of Coronary Artery Geometry and Its Relationship to Coronary Artery Disease, Based on Coronary CT Angiography

Abstract: To investigate the relationship between dynamic changes of coronary artery geometry and coronary artery disease (CAD) using computed tomography (CT). Seventy-one patients underwent coronary CT angiography with retrospective electrocardiographic gating. End-systolic (ES) and end-diastolic (ED) phases were automatically determined by dedicated software. Centerlines were extracted for the right and left coronary artery. Differences between ES and ED curvature and tortuosity were determined. Associations of change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…For example, radius gradient of the plaque, which reflects longitudinal lesion asymmetry, has been proven to be associated with the location of plaque rupture and consequent clinical events ( 95 ). The curvature and tortuosity of coronary arteries might be related to the development of atherosclerosis and plaque size ( 96 , 97 ). These secondary parameters and their clinical indication need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, radius gradient of the plaque, which reflects longitudinal lesion asymmetry, has been proven to be associated with the location of plaque rupture and consequent clinical events ( 95 ). The curvature and tortuosity of coronary arteries might be related to the development of atherosclerosis and plaque size ( 96 , 97 ). These secondary parameters and their clinical indication need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous studies, van Zandwijk et al concluded that there was no significant association between the degree of stenosis and plaque types and the dynamic changes observed in geometrical parameters during the cardiac cycle [ 19 ]. Similar to previous study designs, this research group used CCTA with retrospective electrocardiographic gating to acquire end-systolic and end-diastolic phase reconstructions of the coronary vessels and measured curvature and tortuosity for both phases.…”
Section: Technical Considerations On the Description Of Coronary Arte...mentioning
confidence: 68%
“…It was found that curvature was significantly higher in end-systole for both artery and segment level. Tortuosity, on the other hand, was significantly different only at a segment level [ 19 ]. Considering the dynamic changes of geometry throughout the cardiac cycle is expected to add to the study of atherosclerosis development but at the same time introduces more complexity and workload.…”
Section: Technical Considerations On the Description Of Coronary Arte...mentioning
confidence: 99%